2006
DOI: 10.1002/nbm.1026
|View full text |Cite
|
Sign up to set email alerts
|

ProFit: two‐dimensional prior‐knowledge fitting of J‐resolved spectra

Abstract: A two-dimensional fitting procedure is introduced, capable of extracting the full amount of information from 2D J-resolved magnetic resonance spectroscopic data. The fitting procedure uses a linear combination of 2D model spectra. For reducing the degrees of freedom and increasing robustness, it is divided into a non-linear outer loop and an inner linear least-squares fit for the concentrations. In vitro and in vivo experiments on a whole-body 3 T MR scanner show the detectability of a wide range of metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
225
4
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 167 publications
(247 citation statements)
references
References 24 publications
16
225
4
2
Order By: Relevance
“…NAA is typically diminished in AD,17, 18 and this pattern held for this study ( F [2,75] = 7.231, P = 0.001; NAA was lower in the AD than in the younger CN ( P = 0.0003) and older CN groups ( P = 0.022). Metabolite ratios in the normal groups were consistent with those reported earlier in ProFit literature 24. PRESS Creatine levels were not significantly different between groups ( F [2, 43] = 1.106, P = 0.340), suggesting that between‐group differences in the ratios of other metabolites to creatine are not merely attributable to differences in creatine.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…NAA is typically diminished in AD,17, 18 and this pattern held for this study ( F [2,75] = 7.231, P = 0.001; NAA was lower in the AD than in the younger CN ( P = 0.0003) and older CN groups ( P = 0.022). Metabolite ratios in the normal groups were consistent with those reported earlier in ProFit literature 24. PRESS Creatine levels were not significantly different between groups ( F [2, 43] = 1.106, P = 0.340), suggesting that between‐group differences in the ratios of other metabolites to creatine are not merely attributable to differences in creatine.…”
Section: Resultssupporting
confidence: 88%
“…This post hoc analysis retained significance for these comparisons. A pertinent limitation of the J‐PRESS method is that it may overestimate the Glc signal, possibly due to macromolecule contamination 24. However, this would also be true for the two control groups, and there is at the moment no clear evidence of macromolecule differences causing MRS signal differences in AD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Beside glutamate, it shows the detectability of a wide range of metabolites, including myo-inositol, glutathione, scyllo-inositol, GABA, alanine and ascorbic ac [62].…”
Section: Spectral Editingmentioning
confidence: 99%
“…A number of spectral editing techniques have been proposed in an attempt to resolve GABA. The techniques successfully implemented at 3 T include: single quantum difference spectroscopy (SQDS) [64], STEAM with optimized sequence times [65], maximum-echo sampling [48], double-quantum filtering with selective J rewinding [66] and ProFit of J-resolved spectra [62]. The selective homonuclear Hartmann-Hahn transfer method, recently proposed by Choi et al [67], provides a spectral selectivity and a sensitivity greater than those reported by previous GABA-editing methods.…”
Section: Spectral Editingmentioning
confidence: 99%